Readiness for sport: focus on musculoskeletal injuries - Ribeiro Neto, Antônio (2022)
The aim of the study was to determine the prevalence of injuries and to screen these injuries in Crossfit practitioners. The practitioners answered sociodemographic questions related to the practice of the sport, injuries and the Sport Readiness Questionnaire with a Focus on Musculoskeletal Injuries (MIR-Q). Of the 368 practitioners evaluated, 57.33% were women, 54.61% of the practitioners answered YES in at least one of the MIR-Q questions, 48.91% reported injury to at least one body segment. In this study, a positive and moderate relationship between having an injury and a positive result on the MIR-Q was found and practitioners who reported an injury had 2.76 odds to have a positive result on the MIR-Q. The rate of injuries found was similar to other studies with similar populations and that more than half of the sample requires consultation with a specialist, based on the adopted screening method.